THE MOTIF OF ‘DEATH’ IN THE NOVEL “THE PLAGUE OF DOVE” - Mirzayeva Parvina Ulugbek kizi (The Conference Hub, 2025)
Louise Erdrich is widely regarded as one of the most significant and influential voices among Native American authors, making substantial contributions to the second wave of the Renaissance of Native American literature. “The Plague of Doves” by Louise Erdrich, written in 2008, considers the theme of racism prevalent in the twentieth century and its enduring impacts. The following article discusses the dual motifs of death, running in parallel, offering multiple layers of meaning that deepen our understanding and perception of the events unfolding within the story.
Keywords: motif, narration, death, US literature, theme, “The Plague of Dove”, native, indigenous, Ojibwa, Louise Erdrich.